Low chromate diet in dermatology - Sharma Ashimav (Wolters Kluwer Medknow Publications, 2009)
Chromium is an essential trace element found in soil, water, air, and in the biosphere. It is the fourth most common element in the earth′s crust, mostly used to manufacture stainless steel and other alloys. Chromate allergy is not uncommon and its prevalence rate is reported to be 6%. Once developed, it tends to persist for a long time. Chromate is present in most of the dietary items. Chromate content in food often varies considerably from place to place. However, certain foods are routinely high in chromate content. Chromate in the diet of a chromate-sensitive person can provoke dermatitis. Careful selection of food with relatively low chromate concentration can bring a reduction in the total dietary intake of chromate per day. This can influence outcome of the disease, especially chronic vesicular hand eczema due to chromate sensitivity, and can benefit a chromate-sensitive patient.